Penerimaan Sensoris dan Karakteristik Kimia terhadap Teh Herbal Instan: Jahe (Zingiber Officinale), Serai (Cymbopogon Citratus), dan Jeruk Nipis (Citrus Aurantifolia): Penerimaan Sensoris dan Karakteristik Kimia terhadap Teh Herbal Instan: Jahe (Zingiber Officinale), Serai (Cymbopogon Citratus), dan Jeruk Nipis (Citrus Aurantifolia) - Rini Fertiasari; Rizky Brisha Nuary; Nana Kirani (Universitas Airlangga, 2026)
Background: Ginger, lemongrass, and lime possess antioxidant potential, making them suitable for functional beverages. This research used ginger, lemongrass, and lime in the production of instant herbal tea (wedang) with an innovative tea bag packaging to simplify preparation. Objectives: To determine the effects of formulation treatments on the chemical and sensory characteristics of herbal tea. Methods: Prototyping of Jasernis (ginger, lemongrass, and lime) tea bags was conducted from February to June 2024. The research employed formulations of ginger, lemongrass, and lime at ratios of (60%:25%:15%, 60%:15%:25%, and 60%:5%:35%). A randomized complete block design was used because all materials and treatments were applied simultaneously. Sensory testing utilized a hedonic approach, followed by normality testing using SPSS. Data analysis revealed anomalies, necessitating non-parametric Kruskal-Wallis testing. Chemical analyses included moisture content, ash content, pH, and antioxidant activity. Results: Research findings indicate that formulations of ginger, lemongrass, and lime significantly affected moisture content, ash content, pH, antioxidant activity, and sensory parameters (color, taste, aroma, and overall). The best Jasernis tea bag formulation was treatment F3, with 2.4 g ginger, 0.2 g lemongrass, and 1.4 g lime. Panelist preference for the best formulation yielded scores of 4.80 for color, 3.37 for aroma, 3.40 for taste, and 3.93 for overall acceptability. Chemical composition of the Jasernis tea bag included moisture content (11.713%), ash content (5.419%), pH (4.20), and antioxidant activity (419 ppm). Conclusions: Formulations of ginger, lemongrass, and lime significantly affected moisture content, ash content, pH, antioxidant activity, and sensory parameters (color, taste, aroma, and overall).